Plugging the Brain Drain: The Role of Indonesia Diaspora Network towards Indonesian Citizens in Overseas Policy - Afifi Elfinur, Dinny (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2021)
This paper will start from the shifting of brain drain as phenomena and terminology, from traditional (nasionalist) to comprehensive (globalist) thought. The nationalist tends to envisage brain drain as negative impact to source countries while the globalist assumes the ‘brain’ is not drained but circulated and their roots will be embeded as part of their identities. By choosing Indonesia as the case study, this paper will try to analyse about how the brain drain issue related to Indonesia Diaspora Network (IDN) and how the network of IDN works to influence the homeland government with the globalist thought. The Indonesian President Decree No. 76 on 2017 regarding Facilities for Indonesian Citizens in Overseas (Masyarakat Indonesia di Luar Negeri – MILN) designated, on this paper, as new milestone of attainment to Indonesian Diaspora official recogniztion, which enclosed to mission of Indonesia Diaspora Network Global (IDN Global) since its established on 2012. Using the theory of Transnational Advocacy Network by Keck and Sikkink, combined with argument of Sara Kalm on Diaspora Strategies as Technology of Citizenship, this paper argues that the launching of the policy shows that: (i) the role of diaspora network as principal actor who spreads and infused the globalist thought to the government, Indonesia citizens in home countries, and collecting international support, (ii) involving Diasporas in policy making process could be a good strategy for Indonesian Government to instill and strengthen diaspora’s emotions of national obligations, which will also plug the ‘drain’ and maintain to circulate the ‘brain’. To enrich and emphasize these arguments, some literatures of state-diaspora relations will also be applied.